Identification and differentiation of Pleistocene paleosols in the northern Pampas of Buenos Aires, Argentina - Zárate, Marcelo Arístides (2002)
A combined macromorphological and micromorphological approach was used to identify and differentiate paleosols at a representative exposure of the Pleistocene sedimentary succession in the northern Pampas of Buenos Aires (La Plata area). Five pedological units (Pu), which apparently represent four discrete paleosols plus the surface soil, were initially differentiated on the basis of field-scale morphological properties. The succession was divided into B and C horizon with an A horizon only clearly identified in the surface soil and a weak A horizon at depth. Micromorphology suggests a complex pedosedimentary history of welding, with some degree of water reworking indicated by fragments of sorted layers and the significant grain-size heterogeneity of the parent material. The micromorphological data do not support the field differentiation of Pu4, Pu3, and Pu2 into discrete paleosols. Pedological features (i.e. excrements, secondary carbonate coatings, illuvial clay coatings) occur throughout without any obvious breaks or patterns. Pu4, Pu3, and Pu2 are therefore interpreted as an accretionary and/or welded pedocomplex. The Gorina section does not conform to the simple classical model proposed by other authors in the region of alternating loess and paleosol units associated with arid (loess deposition) and wet (soil formation) intervals, respectively.